Stability for Functional Equation of Mixed Type in Non-Archimedean Normed Spaces. (25th February 2014) - Chang, Ick-Soon; Lee, Yang-Hi
Abstract : We take into account the stability of the following functional equationf ( x + a y ) + f ( x - a y ) - 2 f ( x ) - a 2 f ( y ) - a 2 f ( - y ) = 0 in non-Archimedean normed spaces.